2017 IEEE Winter Conference on Applications of Computer Vision (WACV) 2017
DOI: 10.1109/wacv.2017.93
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Local Context for Multi-target Tracking in Wide Area Aerial Surveillance

Abstract: Abstract. Tracking many vehicles in wide coverage aerial imagery is crucial for understanding events in a large field of view. Most approaches aim to associate detections from frame differencing into tracks. However, slow or stopped vehicles result in long-term missing detections and further cause tracking discontinuities. Relying merely on appearance clue to recover missing detections is difficult as targets are extremely small and in grayscale. In this paper, we address the limitations of detection associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…For the exemplary configurations, best performance is achieved by Median BG + N for q = 0.0036 with an f-score of 0.773 after tracking and a MOTA value of 0.611. In comparison to a recent survey on trackers for persistent tracking in WAMI data [2], where the trackers proposed by Chen et al [2], Reilly et al [6], and Prokaj et al [1] achieved best results with MOTA values of 0.599, 0.522, and 0.493, respectively, this demonstrates state of the art performance of the proposed tracking framework. A more detailed performance comparison, which is based on the same evaluation sequence and code also used in [2] to ensure comparability of results, can be found in [3].…”
Section: Detection and Tracking Performancesupporting
confidence: 50%
See 3 more Smart Citations
“…For the exemplary configurations, best performance is achieved by Median BG + N for q = 0.0036 with an f-score of 0.773 after tracking and a MOTA value of 0.611. In comparison to a recent survey on trackers for persistent tracking in WAMI data [2], where the trackers proposed by Chen et al [2], Reilly et al [6], and Prokaj et al [1] achieved best results with MOTA values of 0.599, 0.522, and 0.493, respectively, this demonstrates state of the art performance of the proposed tracking framework. A more detailed performance comparison, which is based on the same evaluation sequence and code also used in [2] to ensure comparability of results, can be found in [3].…”
Section: Detection and Tracking Performancesupporting
confidence: 50%
“…As trackers solely relying on moving object detections fail when targets slow down or become stationary, developing methods for persistent tracking has recently become a focus of research interest in the WAMI community. To handle long-term missing motion detections, Prokaj et al [1] and Chen et al [2] combine a detection-based tracker with a regression tracker and with a local context tracker, respectively. In [3] it is demonstrated that state of the art results can also be achieved with a MHT-based single-tracker framework that avoids the additional complexity introduced by frameworks based on two trackers and recovers missing motion detections with a classifier-based detector.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…For the areas with heavy traffic, a lightweight regression network is trained to predict the centre of multiple moving objects from individual detections. This approach of combining the CNNs' and background subtraction's outputs makes it possible for the shape of moving objects to be obtained: this can be useful information that can be exploited by appearancebased tracking systems (e.g., [17], [18]). Finally, in addition to comparing the detections with the ground-truth, we applied a Gaussian Mixture Probabilistic Hypothesis Density (GM-PHD) filter to the detections to directly utilise the product of the proposed algorithm.…”
Section: Introductionmentioning
confidence: 99%